Enhancing Motivation in Reserve Component Basic Military Training through Public Administration Strategies - Niwadi, Ramli; Ikbal, Muhammad; Hamid, Hariyanti (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research explores the motivations behind university students' involvement in Basic Military Training activities for the Reserve Component, revealing a concerning lack of enthusiasm despite established regulations. Using qualitative methodology and NVivo 12 Plus for analysis, this study identified two important factors that shape motivation levels: environmental influences and personal influences. Although environmental factors played a role, it was intrinsic motivation that emerged as the main determinant. Highlighting the importance of nurturing intrinsic motivation, the study advocates interventions such as motivational workshops, mentorship programs, and customized reward initiatives for college students. These interventions aspire to foster a culture of proactive engagement in national defense efforts. The findings underscore the existence of gaps in the motivation levels of students at Universitas Muhammadiyah Sidenreng Rappang regarding basic military training for the reserve component. Nevertheless, through strategic public administration initiatives aimed at fostering intrinsic motivation, the university has the potential to galvanize students, empowering them to actively contribute to the country's defense readiness and efficacy, thereby enhancing the capabilities of the reserve component.